Kompetensi Khas di Sektor Pariwisata - Annisa Retno Utami (Faculty of Economic and Business, 2016)
The Distinctive Competencies at Tourism SectorEvery company should have powers that are not easily imitated by competitors, so that the company can be have distinctive competence. Distinctive competence within an organization include labor skills and abilities of resources. This article explains the distinctive competence and understanding of the particulars of distinctive competencies in the tourism sector. The method in this paper with study literature or librabry research of International and National journals. In tourism sectors, distictive competence can be developed with authenticity attraction, culture/heritage, infrastructure, support activities, additional facilities (shopping), entertainment, special event/festival, quality service, destination management, location, price, and security. This article is expected to be a consideration for managers to create tourist attraction. Tourist attraction is one strategies used to attract the attention of tourists. Strategies used to be different from other attractions, so that the attraction has it uniquenessDOI: 10.15408/ess.v6i1.3122